El control de inversiones en la UE y los EE.UU. Diferentes modelos - ¿Los mismos objetivos? - Arp, Björn (Pontificia Universidad Católica del Perú, 2023)
This article analyzes the control of foreign investments carried out in recent years by the US and the European Union (EU). This analysis is justified because for only about five or six years on both sides of the Atlantic, the control of investments that reach these territories has been strengthened. The article clarifies and compares the scope of investment control in each of these two territories. This study allows us to observe the risks of a progressive expansion of the notion of “national security”, and especially in the EU - due to the decentralized nature of investment control - to a political use with an impact on relations between Member States and EU bodies, including the judicialization of the definition of national security and public order through the intervention of the Court of Justice of the EU. In addition, investment screening may impact the EU-US trade and investment relations.

Este artículo analiza el control de inversiones extranjeras efectuado en años recientes por los EE.UU. y por la Unión Europea (UE). Este análisis se justifica porque desde hace apenas unos cinco o seis años a ambos lados del Atlántico se ha reforzado el control de inversiones que llegan a estos territorios. El artículo clarifica y compara el alcance del control de inversiones en cada uno de estos dos territorios. Este estudio permite observar los riesgos de una progresiva expansión de la noción de “seguridad nacional”, y especialmente en la UE —debido al carácter descentralizado del control de inversiones— a un uso políticamente condicionado que puede tener impacto en las relaciones entre los Estados miembros y los órganos de la UE, incluida la judicialización de la definición de seguridad nacional y orden público a través de la intervención del Tribunal de Justicia de la UE, y entre los EE.UU. y la UE.
The control of investments in the EU and the USA. Different models - ¿same objectives?
Keywords: Investment control; EU law; International relations; Globalization; National security; Control de inversiones; Derecho de la UE; Relaciones internacionales; Globalización; Seguridad nacional; Orden público; https://purl.org/pe-repo/ocde/ford#5.05.00